Peran Inovasi Digital dan Teknologi Keuangan Syariah (Fintech, Crowdfunding dan P2P Lending) dalam Mendukung Green Banking di BSI Padang - Yetti, Febri Delmi; Jasmina Syafei (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the role of digital innovation and Islamic financial technology (fintech, crowdfunding, and P2P lending) in supporting green banking practices at BSI Padang. This study uses a qualitative approach with a case study to analyze the integration strategy of digital innovation and Islamic finance in environmentally friendly banking practices at BSI Padang. Data collection was carried out through observation, interviews with internal and external parties of BSI, and documentation studies, with researchers present directly in the field. Data analysis used the Miles and Huberman model, with validity maintained through triangulation, member checks, audit trails, and peer debriefing to ensure that the findings reflect real conditions in the field. The results of the study show that BSI Padang has succeeded in integrating digital innovation and Islamic financial technology to support green banking practices. Innovations such as BSI Mobile, Islamic crowdfunding, and P2P lending are implemented strategically to improve service access, time efficiency, and reduce the use of physical documents. Acceptance of innovation is strengthened through education, training, and financial literacy campaigns. In addition, the commitment to sustainability is reflected in green MSME financing and CSR programs that focus on the environment.